Concentration and distribution of B and Se in stream sediments of Zambia and their agricultural implications - Sun, Hongwei; Ren, Junping; Wang, Jie; Zuo, Libo; He, Fuqing; Wu, Xingyuan; Xu, Kangkang; Mukofu, Chipilauka; Dokowe, Alphet Phaskani; Cao, Shuping (Frontiers in Earth Science, 2025)
The country's national scale geochemical mapping can provide crucial geochemical support for Zambia's foundational geology, agricultural productivity, environmental conservation, mineral exploitation, and other domains. This study aims to determine the overall abundance and regional distribution of B and Se in Zambian stream sediments, as well as their impact on the environment and on the agricultural output. The median concentrations of B and Se are 12.74 and 0.056 μg/g, respectively. While the concentration of Se was more noticeable, the distribution patterns of B concentration seemed to be more consistent and lacked distinct indicators for agricultural output. It also offers more robust recommendations for future land planning and agricultural growth. In comparison to other tectonic belts, the Domes Region, Lufilian Arc and Choma-Kalomo Block have greater median and average concentrations of Se. Black shales and vast epithermal metallogenic zones are common in the Kawana-Solwezi-Ndola and the Mansa-Mporokoso- Kasama regions, which also have high Se contents. These regions could serve as promising places for the advancement of selenium-enriched agricultural practices.